A Children's Book about Being Lazy - Berry, Joy Wilt.; Costanza, John (Chicago : Grolier, 1988)
Explains what it means to be lazy and why it is better to be helpful, than lazy.
3.6
K-3
Keywords: Laziness -- Juvenile literature; Helping behavior -- Juvenile literature; Laziness; Helpfulness; Human behavior; Helping behavior